Patterns for searching data on the web across different research communities - Borst, Timo; Limani, Fidan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
Being a concept quite familiar in the domain of information retrieval, data search in a web based environment has recently gained attention. With researchers and academic institutions increasingly publishing their data on the public web, traditional research workflows with respect to data search are subject to empirical analysis, user studies, re-engineering and service development. We investigate these workflows more into detail and introduce three patterns of web-based data search intended to serve both as a general reference and as a starting point for discipline specific adoptions. We give some real-world examples in terms of existing web applications and GUI components, thereby suggesting a combination of both generic and community specific approaches towards solutions for data search. We further analyze these patterns by means of empirical evidences we found in some research communities, before giving a summary and outlook on future work.